Construction and Stability of Riesz Bases - Yulin Bai; Wanyi Wang; Guixia Wang; Suqin Ge (Journal of Function Spaces)
We construct some new Riesz bases and consider the stability of them. The investigation is based on the stability of Riesz bases of cosines and sines in the Hilbert space L2[0,π].